2020
DOI: 10.3390/genes11080882
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Spectrum and De Novo Mutation Analysis in Stickler Syndrome Patients with High Myopia or Retinal Detachment

Abstract: Stickler syndrome is a connective tissue disorder that affects multiple systems, including the visual system. Seven genes were reported to cause Stickler syndrome in patients with different phenotypes. In this study, we aimed to evaluate the mutation features of the phenotypes of high myopia and retinal detachment. Forty-two probands diagnosed with Stickler syndrome were included. Comprehensive ocular examinations were performed. A targeted gene panel test or whole exome sequencing was used to detect the mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Exome libraries were enriched and sequenced on the Illumina HiSeq 2000 Genome Analyzer (Illumina, San Diego, CA, USA), using a HiSeq Sequencing Kit (Illumina) according to the manufacturer’s instructions. Bioinformatic analyses were made as described previously [ 34 , 35 , 36 , 37 ]. Based on the possible inheritance models of AF in the pedigree ( Figure 1 A), the variants that did not match any reasonable inheritance pattern of AF were filtered out.…”
Section: Methodsmentioning
confidence: 99%
“…Exome libraries were enriched and sequenced on the Illumina HiSeq 2000 Genome Analyzer (Illumina, San Diego, CA, USA), using a HiSeq Sequencing Kit (Illumina) according to the manufacturer’s instructions. Bioinformatic analyses were made as described previously [ 34 , 35 , 36 , 37 ]. Based on the possible inheritance models of AF in the pedigree ( Figure 1 A), the variants that did not match any reasonable inheritance pattern of AF were filtered out.…”
Section: Methodsmentioning
confidence: 99%
“…It has an estimated prevalence of 1-3 in 10,000 [53]. This disorder can be caused by either AD inherited mutations of collagen type 2, collagen type 11, and lysyl oxidase or by AR inherited mutations in collagen type 9 and lysyl oxidase [13]. The most commonly seen mutations are in COL2A1 (STL type 1) and COL11A1 (STL type 2) [13].…”
Section: Stickler Syndromementioning
confidence: 99%
“…Ocular findings include myopia, cataracts, vitreous alterations, glaucoma, and retinal detachments (Table 3) [52,75]. Huang found that 76% had high myopia (>−6D), and 69% had retinal detachment, many of which had a COL2A1 mutation [13]. One study found in COL2A1 mutations that 89% had myopia, 42% had vitreous abnormalities, and 55% had at least one retinal detachment [52].…”
Section: Stickler Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…These variants cause a dominant-negative effect that dramatically impairs homotrimer assembly and stability, leading to growth bone alterations and severe phenotypes such as ACG2 and hypochondrogenesis. In contrast, nonsense mutations or out-of-frame deletions can cause a premature stop codon that leads to haploinsufficiency, resulting in a decrease in collagen synthesis, as well as diseases with milder phenotypes than that observed in ACG2 [7,11]. Splice site variants leading to an in-frame deletion of COL2A1 have already been described and are mainly associated with Kniest dysplasia [12,13].…”
Section: Introductionmentioning
confidence: 99%